The Khovanov-Lauda 2-Category and Categorifications of a Level Two Quantum SL(N) Representation - David Hill; Joshua Sussan (International Journal of Mathematics and Mathematical Sciences)
We construct 2-functors from a 2-category categorifying quantum sl(n) to 2-categories categorifying the irreducible representation of highest weight 2ωk.